As publicações científicas do Instituto Oswaldo Cruz no período 1900 a 1917: um estudo exploratório - Weltman, Wanda Latmann (1992)
Exploratory study analysing the scientific production of the Oswaldo Cruz Institute (IOC), in the period 1900-1917. The study attempts the caracterization of the inicial production of the Institute and the performance of their scientists. Scientists working at IOC during that time are identified, as well as their respective specialities, publications, and citation behaviour. By means of comparisons between publication data and citation data, some aspects of their behaviour as information producers and users are evaluated.